pls help me with this simple step

i dont know how that last step came,

Printable View

- Mar 8th 2010, 04:41 AMavengerevengestuck in a simple step after differentiation.
pls help me with this simple step

i dont know how that last step came, - Mar 8th 2010, 05:50 AMJester
From what you have

$\displaystyle

y - a \sin ^3 t = - \tan t \left(x - a \cos ^3 t\right)

$

$\displaystyle

y \cos t - a \sin^3t \cos t = - x \sin t + a \cos^3t \sin t

$

$\displaystyle

y \cos t = - x \sin t +a \sin^3t \cos t + a \cos^3t \sin t

$

$\displaystyle

y \cos t = - x \sin t +a \sin t \cos t\left( \underbrace{\cos^2t + \sin^2t}_{=1}\right)

$

so

$\displaystyle

y \cos t = - x \sin t +a \sin t \cos t$. - Mar 8th 2010, 06:08 AMavengerevengethanks
i know this is very simple step but it was not coming,

thankss